Financial policies and capital markets in Arab countries - El-Naggar, Said (Washington, D.C. : International Monetary Fund, 1994)
In recent years the process of financial liberalization has spread in both developed and developing countries. This liberalization has been accompanied by increased global financial integration, which has led to a great expansion of cross-border capital flows. The impact of these developments on the economies of the Arab region and their prospects for the future were the focus of a seminar held in Abu Dhabi on January 25-26, 1994. In sponsoring the seminar, the IMF was again happy to be associated with the Arab Monetary Fund and the Arab Fund for Economic and Social Development, as well as with the International FinanceCorporation. The present volume of seminar proceedings is the sixth to have been published jointly by the IMF and the Arab Monetary Fund and provides a most timely addition to the series. Once again, Professor Said El-Naggar moderated the seminar and brought his considerable experience to bear on managing the discussion as well as on preparing the proceedings for publication.
'papers presented at a seminar held in Abu Dhabi, UAE, January 25-26, 1994.
Includes bibliographical references.
gau 02/08/2016
Loan
Keywords: Finance; Monetary policy; Capital movements; Capital market; Financial institutions; Arab countries